2021
DOI: 10.3390/s21227540
|View full text |Cite
|
Sign up to set email alerts
|

Body Temperature Monitoring for Regular COVID-19 Prevention Based on Human Daily Activity Recognition

Abstract: Existing wearable systems that use G-sensors to identify daily activities have been widely applied for medical, sports and military applications, while body temperature as an obvious physical characteristic that has rarely been considered in the system design and relative applications of HAR. In the context of the normalization of COVID-19, the prevention and control of the epidemic has become a top priority. Temperature monitoring plays an important role in the preliminary screening of the population for feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…However, this does not mean that no patient had a high temperature, since several of the patients had an elevated skin temperature on the second day, which might be due to inflammation. In addition, it is reported that fever is one of the prominent clinical symptoms of novel coronavirus patients [20]. Moreover, the decrease in temperature (3 rd day) may be due to the patients being given antipyretic drugs as a part of the hospital treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not mean that no patient had a high temperature, since several of the patients had an elevated skin temperature on the second day, which might be due to inflammation. In addition, it is reported that fever is one of the prominent clinical symptoms of novel coronavirus patients [20]. Moreover, the decrease in temperature (3 rd day) may be due to the patients being given antipyretic drugs as a part of the hospital treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, Zhu [105] presented a wearable device with inertial and temperature sensors that may be utilized to apply human behavior recognition (HAR) to body surface temperature detection and correction during COVID-19. The sensing device used a microcontroller, a 6-axis sensor, and a temperature sensor to collect data from ten different users in four distinct daily activity situations.…”
Section: Monitoring and Tracking Methodsmentioning
confidence: 99%
“…IoT devices are able to measure specific human physiological parameters such as heart rate (HR), respiration rate (RR) and blood pressure (BP), electrocardiogram (ECG), Electroencephalogram (EEG), electromyography (EMG), body temperature, Oxygen levels, blood glucose (BG), and the volume of air inspired and expired by lungs (Swayamsiddha and Mohanty, 2020;Chakkor et al, 2021b;Zhang et al, 2021), so that the early diagnosis and necessary treatment can be given One proposed system leverages IoT devices as part of its architecture to actively monitor users data and send this data to heath care centers for evaluation. Also, there are relatively new measurements that monitor the users' heart rate, number of daily steps and sleep time to scan pre-symptomatic cases of COVID-19 for the same purpose-early diagnosis and timely necessary treatment (Josephine et al, 2020;Lo and Sim, 2021;Ni et al, 2021b;Dadon et al, 2022).…”
Section: Detection and Monitoringmentioning
confidence: 99%
“…Detection and monitoring (Arun et al, 2020;Choyon et al, 2020;Dhadge and Tilekar, 2020;Ding et al, 2020;Hossain et al, 2020;Josephine et al, 2020;Karthi and Jayakumar, 2020;Seshadri et al, 2020;Swayamsiddha and Mohanty, 2020;Al-Emran and Ehrenfeld, 2021;Anjali et al, 2021;Ashwin et al, 2021;Awotunde et al, 2021Awotunde et al, , 2022Chakkor et al, 2021a,b;Elbasi et al, 2021;Lo and Sim, 2021;Lubecke et al, 2021;Mukati et al, 2021;Mumtaz et al, 2021;Ni et al, 2021b;Peladarinos et al, 2021;Rehman et al, 2021;Tan et al, 2021;Uddin et al, 2021;Zhang et al, 2021;Dadon et al, 2022;Goergen et al, 2022) Contact tracing Indoor contact tracing (Jeong et al, 2019;Dmitrienko et al, 2020;Kumar et al, 2022;Li et al, 2020b;Otoom et al, 2020;Schmidtke, 2020;Thangamani et al, 2020;Abueg et al, 2021;Lo and Sim, 2021;Mcheick et al, 2021;Wojtusiak et al, 2021) Outdoor contact tracing (Elbir et al, 2020;Maghdid and Ghafoor, 2020;Ting et al, 2020;…”
Section: Section Category Referencesmentioning
confidence: 99%